TUGAS DAN FUNGSI DINAS PARIWISATA, KEBUDAYAAN, PEMUDA DAN OLAHRAGA DALAM UPAYA PENGEMBANGAN OBYEK WISATA KABUPATEN SRAGEN - Liliek Winarni, Agathon Setyo Asmoro, Qomarudin & (Transformasi, 2016)
Tourism is one of industry which is able to real income of a regency.this can be seen because adeveloping regency is influent by touris factor. Sragen regency has several potencial factor,oneof them is tourism. It has several tourist object and they are very attractive whose specialdestination. There for, this reseach is aimed to fine and to describe the duty and function oftourism, youth and sport office in the effort of tourism object development in Sragen Regency.The method of reseach uses qualitative reseach. Method which is used to reseach naturalsituation. It placed the reseach is a key instrument, the tecknique of collection data will be donecombinely, inductive analisys, and the result of the reseach is more meaning than generalizingqualitative. The duty and function is a task which is done by institution it is stated. Tourism,cultur, youth and sport does the duty and function in partly regency state which is based onautonomic principle and has a task to support in the tourism, cultur, youth and sport. By doingthe best duty and function, it can develope and be a developing and organisation of touristobject in definitive by regency is going to regulary move and the economic activity in tourismsector is going to increased shoothly and in the end it is going to result several income. Thebest duty and function makes tourist object development has increased valve of the real incomeof regency and the local tourism development. Based in the research and analysis the data, theresult the reseach can be categirized as a good for the duty and function of tourism, culture,youth and sport office inthe effort of tourist object developing of Sragen Regency.Key word : Tourism, Human Resources, The Duty And Function